Double-Blind Peer Review of Paragraph Writing in EFL Class - Adhitya Wahyu Pradana; Tatik Irawati (ELITE Association Indonesia, 2023)
The purpose of this study is to describe how double-blind peer review implementing in student paragraph writing classes of English students at STKIP PGRI Jombang. This study uses the phenomenon of qualitative descriptive data aims to identify student writing descriptive text performance from English classes in descriptive text and content analysis procedure. The expert reviewers are English lecturers in the same field of English language teaching. The result of this research double-blind peer review works well to present valid data about students’ writing performance in paragraph writing class, especially in their descriptive, and found some novelty. The research novelty of students writing often begin texts (is, are, has, have, been to) with connecting verbs or relational processes to categorize and describe appearances or characteristics. Second, Use mental verbs or mental processes when describing emotions. Third, use adjectives and adverbs to add information to nouns (participants) and verbs (actions) to provide a more detailed description of the subject and make the text clearer. Fourth, Use adverb phrases to add more type, place, or time information. To make the text easier to read, it is sometimes achieved with contextual embedded sentences. Keywords: Double-Blind Peer Review, Paragraph Writing, Writing Skill